PERANCANGAN ULANG ANTARMUKA PORTAL KITALULUS DENGAN MENGGUNAKAN METODE USER CENTERED DESIGN (UCD) - Ghinna Yumna Rahayu; Aviarini Indrati (Asosiasi Dosen Muda Indonesia, 2024)
KitaLulus is a trusted job portal platform with more than 3 million job seeker, however there are still problems that affect job seeker in the application process. Therefore, it is necessary to analyze the function of this portal to see whether it is running well and in accordance with user requirements so that solutions can be remomended. The aim of this research is to analyze the user interface and redesign the interface to produce a prototype according to the user requirements and experience of job seeker on job portal of KitaLulus. The method of this research is User Centered Design (UCD) that consists of 4 stages, namely understanding the context of use, determining user needs, designing solutions and evaluating requirements. The first step is understanding the context that it is to analyze the level of user usability using the WEBUSE questionnaire and interviews with job seekers of the KitaLulus portal. The second stage, determine user needs that it is to identify problems and requirements of user interface. The third stage is design solution, that it is redesign of user interface prototype based on user requirements and experiences. The final stage is evaluation of requirements, to evaluate the prototype to find out improvements in usability. The research results show that the prototype has an average value of 0.877. It shows an increase of 0.144 and change in usability level from Good to Excellent.